The Influence of Return On Assets (ROA) and Return On Equity (ROE) On Sharia Stock Prices (Case Study of Companies Registered on JII 2016-2019) - Astuti, Puji; Hilyatin, Dewi Laela; Intansari, Anggita Isty; Hadi, Rahmini (Islamic Economic Scholar Association and Faculty of Economics and Business Universitas Jenderal Soedirman, 2024)
An important decision faced by an investor in deciding to include capital in the company is to be able to choose the right company because stock conditions often fluctuate and are uncertain. Then, it can be done using market ratio analysis, which can help investors determine which company to choose. This study aims to determine the partial and simultaneous effect of Return On Assets (ROA) and Return On Equity (ROE) on stock prices in the group Jakarta Islamic Index. The population in this study consisted of all issuers in the Jakarta Islamic Index (JII), which amounted to 30 companies. The purposive sampling technique was used to obtain 14 companies as research samples. The observation period is four years, namely in 2016-2019, so the unit of analysis obtained is 56. The research variables consist of the independent variables ROA (X1) and ROE (X2) and Stock Price (Y) as the dependent variables. The data collection method in this research is the documentation method. The data analysis technique used is multiple linear regression. Based on the results of the regression analysis, it can be seen that ROA and ROE simultaneously had an effect on Islamic stock prices in the JII group in 2016-2019. Partially, ROA did not affect Islamic stock prices in the JII group in 2016-2019. While ROE partially affected the price of sharia shares in the JII group in 2016-2019.